Theoretical analysis for the data immigration between memory and processor percolation cache - Jiuchuan HU; Dongrui FAN; Jiancong CHENG; Long YAN; Xiaochun YE; Lingzhi LI; Liangyi WAN; Haibin ZHONG (Tongxin xuebao)
To improve the computer processor’s memory access efficiency, increase hit rates, reduce data fetching latency, the data and instructors that had close relation with each other could build the just-in-time locality environment on processor’s cache.To build such an environment, the relations between the data and instructors should be studied while them being immigrated into on-chip cache.The research results show that these relations could be well kept when the data and instructors are moved.The simulation also shows that the percolation cache can help the processor core to increase its hit rates.These research results give a new way to build the just-in-time locality environment on the percolation cache.